2014
DOI: 10.4314/ajid.v8i2.5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hepatitis C virus antibody among undergraduates in Ogbomoso, Southwestern Nigeria

Abstract: Background: This study was conducted to determine the prevalence of hepatitis C virus antibody (anti-HCV), among a healthy university undergraduate population in south-western Nigeria. Materials and Methods: Relevant medical information of students who underwent the post-admission screening exercise for the year 2012, at the Ladoke Akintola University of Technology (LAUTECH), Health Center, Ogbomoso were extracted from the laboratory log book. All tests were done using rapid anti-HCV test kit by Health -Chem d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
9
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 10 publications
6
9
6
Order By: Relevance
“…Data obtained in healthcare settings has been associated with a higher prevalence attributable to symptomatic individuals who are likely to contribute to a large extent to subjects tested compared to community based studies which mostly comprise apparently well individuals. Our relatively high prevalence also contrasts to the low prevalence ranging between 0-1 percent reported by studies involving healthy subjects [13,14].…”
Section: Author Contributionscontrasting
confidence: 99%
“…Data obtained in healthcare settings has been associated with a higher prevalence attributable to symptomatic individuals who are likely to contribute to a large extent to subjects tested compared to community based studies which mostly comprise apparently well individuals. Our relatively high prevalence also contrasts to the low prevalence ranging between 0-1 percent reported by studies involving healthy subjects [13,14].…”
Section: Author Contributionscontrasting
confidence: 99%
“…20 However, Atshaha et al in Ethiopia recorded history of hospitalisation, tooth extraction and blood transfusion. 21 The common cluster of risk factors (unprotected multiple sex, sacrification/tattooing, blood transfusion) recorded in this study is a common feature of most studies in Nigeria 19 and some part of Africa. 22 This could be explained by characteristics of African society where sacrifications are embedded in their custom/lifestyle for the service or worship of a deity.…”
Section: Discussionmentioning
confidence: 67%
“…Blood transfusion was the least occurring risk factor but most accessed. A previous report recorded blood transfusion in Ogbomosho South‐western Nigeria as the common risk factor . This indicates that high risk of exposure, socio‐demographic and lifestyle changes may have contributed to the variation in the frequency of these risk factors.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Despite the low national prevalence rate, several studies in the past have shown that there is a wide disparity in HCV seroprevalence among different population groups and subgroups in Nigeria. 26 There are at least 11 reported cases of HCV transmission attributed to digestive endoscopy. 16,21,[27][28][29][30][31][32][33] Apart from temporal association, serious attempt was made to establish patient-topatient transmission by nucleotide sequencing only in six of these patients.…”
Section: Resultsmentioning
confidence: 99%